Full-length RNA-Seq of the RHOH gene in human B cells reveals new exons and splicing patterns - Frédéric Leprêtre; Jean-Pascal Meneboo; Céline Villenet; Laure Delestré; Bruno Quesnel; Carl Simon Shelley; Martin Figeac; Sylvie Galiègue-Zouitina (Scientific Reports)
Abstract The RhoH protein is a member of the Ras superfamily of guanosine triphosphate-binding proteins. RhoH is an atypical Rho family member that is always GTP-bound and thus always activated. It is restrictively expressed in normal hematopoietic cells, where it is a negative regulator of cell growth and survival. We previously analyzed the RHOH gene structure and demonstrated that this gene is composed of 7 exons, one single encoding exon located at the 3ʹ extremity of the gene, preceded by 6 noncoding exons. To further understand the transcription events associated with this gene, we performed full-length RNA-Seq on 12 B-cell lines. We identified new exons, new splice events and new splice sites, leading to the discovery of 38 RHOH mRNA molecules, 27 of which have never been described before. Here, we also describe new fusion transcripts. Moreover, our method allowed quantitative measurements of the different mRNA species relative to each other in relation to B-cell differentiation.